2014
DOI: 10.1111/jcmm.12219
|View full text |Cite
|
Sign up to set email alerts
|

Arecoline‐induced myofibroblast transdifferentiation from human buccal mucosal fibroblasts is mediated by ZEB1

Abstract: Oral submucous fibrosis (OSF) is considered as a pre-cancerous condition of the oral mucosa and is highly associated with habitual areca quid chewing. Arecoline is the major alkaloid in areca quid and is thought to be involved in the pathogenesis of OSF. Our previous studies have demonstrated that arecoline could induce epithelial–mesenchymal transition (EMT)-related factors in primary human buccal mucosal fibroblasts (BMFs). Therefore, we investigated the expression of zinc finger E-box binding homeobox 1 (ZE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
129
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(132 citation statements)
references
References 35 publications
3
129
0
Order By: Relevance
“…26 Our previous study has demonstrated that ZEB1 could bind to the E-box domain of a-SMA promoter to induce myofibroblast transdifferentiation activities in OSF. 11 However, the detailed molecular mechanisms involved in the regulatory links between Twist-mediated EMT and myofibroblast in OSF are still poorly understood. In this study, we attempted to investigate the role of Twist in the pathogenesis of areca quid chewing-associated OSF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Our previous study has demonstrated that ZEB1 could bind to the E-box domain of a-SMA promoter to induce myofibroblast transdifferentiation activities in OSF. 11 However, the detailed molecular mechanisms involved in the regulatory links between Twist-mediated EMT and myofibroblast in OSF are still poorly understood. In this study, we attempted to investigate the role of Twist in the pathogenesis of areca quid chewing-associated OSF.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have demonstrated that arecoline could induce myofibroblast activities in BMFs. 1,11 Targeting sh-Twist-1 abrogated arecoline-induced collagen gel contraction ( Figure 2C) and migration abilities ( Figure 2D) in BMFs.…”
Section: Knockdown Of Twist Suppresses Arecoline Induced Collagen Conmentioning
confidence: 92%
“…Therefore, Hu and Jian (2007) proposed that EMT was a new possible mechanism of OSF. Subsequently, a recent report clearly demonstrated that Zinc finger E-box binding homeobox 1 (ZEB1), a transcriptional repressor of E-cadherin, was increased in OSF tissues and was induced by arecoline in buccal mucosal fibroblasts followed by induction of myofibroblast activity (Chang et al 2014). Heme oxygenase-1 (HO-1) expression was significantly higher in OSF specimens, and it is expressed mainly by fibroblasts, endothelial cells and inflammatory cells ).…”
Section: Toxicologymentioning
confidence: 99%
“…Our previous studies have demonstrated that arecoline could induce myofibroblast activities in BMFs1119. To further investigate whether SSEA-4 plays a role in maintaining arecoline-induced myofibroblastic differentiation activity, loss-of-function of ST3GAL2 was conducted in arecoline-stimulated BMFs.…”
Section: Resultsmentioning
confidence: 99%
“…Arecoline, the major areca nut alkaloid, could activate the transdifferentiation of oral keratinocytes into myofibroblasts8. Previously, we have also identified that the treatment of arecoline could induce myofibroblasts activities in human normal buccal mucosal fibroblasts (BMFs)91011, supporting the crucial roles of myofibroblasts transdifferentiation during the pathogenesis of OSF.…”
mentioning
confidence: 79%